Preparation method of molybdenum-doped vanadium-manganese-sodium phosphate-based positive electrode material
By doping molybdenum elements in sodium vanadium manganese phosphate to form Na4-2xMn1-2xMoxV(PO4)3/C material, the electronic conductivity difference and cycle stability of sodium vanadium manganese phosphate-based material was solved, and the problem of the electron conductivity difference and cycle stability of the sodium vanadium manganese phosphate-based material was significantly improved. Application performance in wide temperature domain.
Patent Information
- Application Number
- CN202411845710.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-01-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The sodium ion battery positive electrode material vanadium manganese phosphate sodium-based materials have problems such as poor in intrinsic electronic conductivity, Jiang Taylor distortion and trivalent manganese ion dissolution, which limits its application performance in a wide temperature domain.
The high-priced molybdenum element is used to dopant in situ at the manganese site of vanadium manganese phosphate to form a molybdenum-doped vanadium manganese sodium phosphate-based positive electrode material. The general structure is Na4-2xMn1-2xMoxV(PO4)3/C, and is pre-fired by high temperature and final sintering treatment improves the electronic conductivity and cycling performance of the material.
It effectively improves the cyclic performance of sodium manganese vanadium phosphate and the wide temperature domain sodium storage performance, improves the electronic conductivity, inhibits volume expansion and ginger Taylor distortion, and demonstrates a wider commercial application capability.
Smart Images

Figure CN119306198A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sodium ion batteries, and in particular relates to a method for preparing a molybdenum-doped sodium vanadium manganese phosphate-based positive electrode material. Background Art
[0002] Sodium-ion batteries have become a strong candidate for large-scale energy storage systems due to their low cost, abundant reserves, excellent low-temperature performance, and similar working principles to lithium-ion batteries. Among the positive electrode materials of sodium-ion batteries, sodium manganese vanadium phosphate (Na4MnV(PO4)3) materials, as sodium superion conductor (NASICON) type polyanion compounds, have the advantages of stable three-dimensional open framework structure, high operating voltage, good cycle stability, low cost and environmental protection, which has attracted widespread attention from academia and industry. Therefore, sodium manganese vanadium phosphate-based materials are expected to become an alternative for the commercial application of sodium-ion battery positive electrode materials.
[0003] Sodium-ion batteries face the dual challenges of extreme cold and extreme heat when operating in a wide temperature environment (-40 ℃ to 80 ℃), which seriously troubles their application in the field of large-scale energy storage in all climates. The positive electrode material of sodium-ion batteries is a key factor in determining the performance indicators such as the overall energy density, cycle life and safety of the battery. The ideal positive electrode material should have high redox potential and electronic / ionic conductivity, large reversible capacity, good electrolyte adaptability and safety, excellent structural stability and air stability, low preparation and transportation costs and non-toxicity. At present, the positive electrode materials of sodium-ion batteries can be mainly divided into transition metal oxides, polyanionic compounds, Prussian blue analogs and organic compounds, and the first three categories have entered the early stage of industrialization. For positive electrode materials, at present, the research on sodium vanadium manganese phosphate-based materials is still in its early stages, and still faces problems such as poor inherent electronic conductivity, Jan-Taylor distortion, and dissolution of trivalent manganese ions. Among the existing modification methods, carbon coating is the most direct and lowest-cost method to improve the electronic conductivity of materials. At the same time, ion doping is a relatively simple and very effective modification strategy. However, there is relatively little research on ion doping of sodium manganese vanadium phosphate.
[0004] Therefore, it is of great significance to develop advanced synthesis methods for the industrial production of sodium manganese vanadium phosphate-based cathode materials based on ion doping strategies and explore their wide temperature range performance. Summary of the invention
[0005] In view of the problems existing in sodium manganese vanadium phosphate-based positive electrode materials, the present invention proposes a method for preparing molybdenum-doped sodium manganese vanadium phosphate-based positive electrode materials, aiming to improve the capacity, cycle performance and wide temperature range sodium storage performance of the material.
[0006] In order to achieve the above object, the present invention adopts the following technical scheme: A preparation method of a molybdenum-doped sodium manganese vanadium phosphate-based cathode material, in which high-valence molybdenum elements are in-situ doped into the manganese sites of sodium manganese vanadium phosphate, and the structural general formula is Na 4-2x Mn 1-2x Mo x V(PO4)3 / C (x is the mass fraction of molybdenum doped into the manganese site), including the following steps: (1) Dissolve the sodium source, manganese source, molybdenum source, vanadium source, phosphate source and complexing agent in a suitable solvent, stir into a gel under water bath heating, and obtain a precursor after drying treatment; (2) Grind the materials in step (1) evenly, place them in an Ar atmosphere for pre-sintering first, grind them evenly and then carry out tablet pressing, and then place them in an Ar atmosphere for pre-sintering and then final sintering, and the molybdenum-doped sodium manganese vanadium phosphate-based cathode material can be obtained after grinding evenly.
[0007] Further, the sodium source includes but is not limited to sodium acetate, sodium carbonate, sodium oxalate, sodium bicarbonate, sodium citrate; the manganese source includes but is not limited to manganese acetate, manganese nitrate, manganese oxalate; the molybdenum source includes but is not limited to molybdenum acetylacetonate and ammonium molybdate; the vanadium source includes but is not limited to ammonium metavanadate, vanadium pentoxide, oxovanadium oxalate, vanadium acetylacetonate; the phosphate source includes but is not limited to diammonium hydrogen phosphate, ammonium dihydrogen phosphate, phosphoric acid. A further preferred combination is sodium acetate, manganese acetate, molybdenum acetylacetonate, ammonium metavanadate, ammonium dihydrogen phosphate.
[0008] Further, the sodium source, manganese source, molybdenum source, vanadium source, phosphate source are weighed and mixed according to the elemental molar ratio of sodium:manganese:molybdenum:vanadium:phosphorus of 4:1:1-x:x:3 (0 < x ≤ 0.2). The transition metals are mainly manganese, vanadium, and molybdenum.
[0009] Further, the complexing agent includes but is not limited to citric acid, glucose, ascorbic acid, oxalic acid, oleic acid.
[0010] Further, the molar ratio of the complexing agent to the transition metal elements (manganese, vanadium) in the molybdenum-doped sodium manganese vanadium phosphate-based cathode material is 1:1.
[0011] Further, the solvent includes but is not limited to water, ethanol, tetraethylene glycol.
[0012] Further, the heating temperature is set to 60 - 95 °C.
[0013] Further, the drying method is any one of vacuum drying, freeze drying, spray drying, the temperature is 80 - 200 °C, and the time is 5 - 24 h. Further preferably, the conventional vacuum drying method is used, the preferred temperature is 100 - 130 °C, and the preferred time is 10 - 12 h to more fully evaporate the solvent.
[0014] Furthermore, the pre-sintering temperature is 300-500 °C, the time is 2-5 h, and the heating rate is 2-10 °C min -1 .
[0015] Furthermore, the pressure and diameter of the pre-sintering tableting process are 5-30 MP, respectively.
[0016] Furthermore, the final calcination temperature is 600-800 °C, the time is 5-24 h, and the heating rate is 2-10 °C min -1 .
[0017] Compared with the prior art, the beneficial effects of the present invention are: The present invention utilizes the high valence state, small ionic radius, and strong Mo-O bond of the molybdenum element, and dopes it into the manganese site of sodium manganese vanadium phosphate to form a sodium vacancy structure, thereby improving the intrinsic conductivity and sodium ion deintercalation rate of the sodium manganese vanadium phosphate, and inhibiting its volume expansion and Jan Taylor distortion during charge and discharge, thereby effectively improving the cycle performance and rate performance of the sodium manganese vanadium phosphate, especially the wide temperature range cycle performance, and demonstrating a wider range of commercial application capabilities.
[0018] The preparation method discovered in this invention has the characteristics of good repeatability, simple operation, high cost-effectiveness and environmental friendliness, showing good prospects for industrial application. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 The Na2O3 prepared in Examples 1 and 2 of the present invention with different molybdenum doping contents 4-2x Mn 1-2x Mo x XRD pattern of V(PO4)3 / C sample; Figure 2 The Na prepared in Example 2 of the present invention 3.85 Mn 0.85 Mo 0.075 SEM image of V(PO4)3 / C sample; Figure 3 The Na2O3 prepared in Examples 1 and 2 of the present invention with different molybdenum doping contents 4-2x Mn 1-2x Mo x Conductivity diagram of V(PO4)3 / C sample; Figure 4 The Na2O3 prepared in Examples 1 and 2 of the present invention with different molybdenum doping contents 4-2x Mn 1-2x Mo x The first cycle charge and discharge curve of V(PO4)3 / C cathode material at 0.2C rate in the voltage range of 2.0-3.8 V; Figure 5The Na2O3 prepared in Examples 1 and 2 of the present invention with different molybdenum doping contents 4-2x Mn 1-2x Mo x Rate performance diagram of V(PO4)3 / C cathode material in the voltage range of 2.0-3.8 V; Figure 6 is Na in Examples 1 and 2 of the present invention 4-2x Mn 1-2x Mo x Performance diagram of V(PO4)3 / C cathode material in the voltage range of 2.0-3.8 V at 5C rate for 1500 cycles; Figure 7 is Na in Example 2 of the present invention 3.85 Mn 0.85 Mo 0.075 In-situ XRD pattern of V(PO4)3 / C cathode material; Figure 8 is Na in Examples 1 and 2 of the present invention 4-2x Mn 1-2x Mo x The charge and discharge curves of V(PO4)3 / C cathode material at 60℃ and -30℃; Fig. 9 is Na in Examples 1 and 2 of the present invention 4-2x Mn 1-2x Mo x Performance diagram of V(PO4)3 / C cathode material after 100 cycles at 60°C. Fig.10 is Na in Examples 1 and 2 of the present invention 4-2x Mn 1-2x Mo x Performance diagram of V(PO4)3 / C positive electrode material after 50 cycles at -30 ℃ low temperature. DETAILED DESCRIPTION
[0020] The specific embodiments of the present invention are described in detail below in conjunction with the accompanying drawings. The following contents are only examples and explanations of the present invention, and any modifications or supplements made thereon, or in a similar manner, shall fall within the protection scope of the present invention as long as they do not deviate from the concept of the present invention or exceed the scope defined by the claims.
[0021] Example 1: Preparation of Na4MnV(PO4)3 / C material Sodium acetate, manganese acetate, ammonium metavanadate, and ammonium dihydrogen phosphate were weighed in a ratio of 4:1:1:3 for the molar ratio of sodium:manganese:vanadium:phosphorus, and 3 mmol of citric acid was used as a complexing agent. The molar ratio of the complexing agent to the transition metal (manganese + vanadium) was 1:1. They were dissolved in 70 mL of deionized water, stirred into a gel state under heating at 80 °C in a water bath, and then placed in a vacuum oven at 120 °C for 12 h. After cooling to room temperature, the powder was ground evenly to obtain a precursor powder. After that, the powder was placed in an Ar atmosphere at 5 °C min -1 The samples were calcined at 400 °C for 4 h at a heating rate of 1.5 ℃ to remove air and organic impurities in the samples. After cooling to room temperature, the samples were ground evenly and placed in a tablet pressing mold with a diameter of 20 mm. The tablets were pressed into tablets at a pressure of 20 MPa to promote the mutual contact between atoms during the subsequent calcination process. Finally, the samples were heated at 5 °C min in an Ar atmosphere. -1 The intermediate product was calcined at a heating rate of 700 °C for 10 h. After cooling to room temperature, the target product was obtained by grinding evenly.
[0022] Example 2: Preparation of Na 4-2x Mn 1-2x Mo x V(PO4)3 / C Materials Sodium acetate, manganese acetate, molybdenum acetylacetonate, ammonium metavanadate, and ammonium dihydrogen phosphate were weighed in a ratio of 4:1-x:x:1:3 for the molar ratio of sodium:manganese:molybdenum:vanadium:phosphorus, 3 mmol citric acid was used as a complexing agent, and the molar ratio of the complexing agent to the transition metal (manganese+vanadium+molybdenum) was 1:1. They were dissolved in 70 mL of deionized water, stirred into a gel state under heating at 80 °C in a water bath, and then placed in a vacuum oven at 120 °C for 12 h. After cooling to room temperature, the powder was ground evenly to obtain a precursor powder. After that, the powder was placed in an Ar atmosphere at 5 °C min -1 The samples were calcined at 400 °C for 4 h at a heating rate of 1.5 ℃ to remove air and organic impurities in the samples. After cooling to room temperature, the samples were ground evenly and placed in a tablet pressing mold with a diameter of 20 mm. The tablets were pressed into tablets at a pressure of 20 MPa to promote the mutual contact between atoms during the subsequent calcination process. Finally, the samples were heated at 5 °C min in an Ar atmosphere. -1 The intermediate product was calcined at a heating rate of 700 °C for 10 h. After cooling to room temperature, the target product was obtained by grinding evenly.
[0023] The following is the preparation of the sodium ion battery pole piece and the preparation of the sodium ion battery using the positive electrode material prepared in the embodiment: (1) Preparation of sodium ion battery electrodes: First, weigh Na according to the mass ratio of 7:2:1 4-2x Mn 1-2x Mo x V(PO4)3 / C, polyvinylidene fluoride binder (PVDF) and acetylene black conductive agent (AB), and add appropriate amounts of 1-methyl-2-pyrrolidone (NMP) solution and zirconium oxide beads, which respectively play the role of adjusting viscosity and assisting mixing, and then form a mixed slurry by vibration ball milling (vibration 8 times, 3 minutes each time). After removing the zirconium oxide beads, the mixed slurry is evenly coated on aluminum foil using a coating tool and vacuumed overnight at 60 ° C. After drying, it is cut into electrode discs with a diameter of 12 mm, and the electrode discs with uniform coating are selected. After weighing the electrode mass, the mass of the active material can be calculated (loading amount ~2 mg cm-2), and then placed in a glove box with a high-purity argon atmosphere for use.
[0024] (2) Preparation of sodium ion batteries: The entire battery assembly process was carried out in a glove box with a high-purity argon atmosphere (water and oxygen concentration <0.1 ppm), and CR2032 button cells were used. The negative electrode shell, negative electrode material, glass fiber separator, electrolyte (~80 μL), positive electrode material, gasket (15.8*1 mm), spring sheet (15.4*1.1 mm), and positive electrode shell were assembled in this order. Metallic sodium (12*0.8 mm) was used as the counter electrode in the half-cell system. Metallic sodium needs to be pretreated before assembling the battery, that is, the active metallic sodium is taken out of the kerosene in the glove box, wiped clean, and rolled into a sodium sheet of uniform thickness, which is then cut into discs with a diameter of 1.2 cm for use. The electrolyte is a 1 M NaClO4 solution of ethylene carbonate / diethyl carbonate (EC / DEC, 1:1 vol.%) with 5 wt.% of fluoroethylene carbonate (FEC) added. However, the electrolyte will precipitate salts and even freeze at low temperatures, so 1 M NaPF6 diethylene glycol dimethyl ether (DIGMYLE) solution was used as the electrolyte in the low-temperature electrochemical performance test. The assembled battery was placed on a battery sealer and a pressure of about 50 kg cm -2 The battery is packaged with a pressure of 10000 μm and left to stand for about 6 h to ensure that the electrolyte has completely infiltrated the interior of the battery before the electrochemical performance test can be carried out.
[0025] Na with different Mo doping contents 4-2x Mn 1-2x Mo x The XRD pattern of V(PO4)3 / C material is as follows Figure 1As shown in the figure, their diffraction peaks all correspond to the standard card of Na4MnV(PO4)3 (PDF#98-042-3538), indicating that molybdenum doping will not change the main crystal structure of Na4MnV(PO4)3, and it has good purity and crystallinity. The right shift of the diffraction peak caused by the increase of molybdenum doping content also shows that the molybdenum element is successfully introduced, resulting in a reduction in the unit cell volume.
[0026] according to Figure 2 The SEM image shows that the prepared material has an irregular micro / nano granular morphology. Figure 3 The Na2O3 with different molybdenum doping contents in the present invention is 4-2x Mn 1-2x Mo x The conductivity of V(PO4)3 / C samples and Na4MnV(PO4)3 / C (NMVP / C) samples were improved after being doped with different molybdenum contents, indicating that molybdenum doping has a positive effect on the electronic conductivity of sodium manganese vanadium phosphate, which is related to the additional hole structure it produces. 3.85 Mn 0.85 Mo 0.075 The conductivity of V(PO4)3 / C, NMMVP / C-0.075) is the most outstanding, and it is expected to show excellent electrochemical performance. However, excessive molybdenum doping (x = 0.1) has limited improvement on the conductivity of NMVP / C, which may be due to the generation of more lattice defects and particle segregation.
[0027] Figure 4 is the Na with different molybdenum doping contents of the present invention. 4-2x Mn 1-2x Mo x The first cycle charge-discharge curves of V(PO4)3 / C cathode materials at 0.2C rate in the voltage range of 2.0-3.8 V. All five materials have two flat voltage platforms at ~3.3 V and ~3.5 V, corresponding to V 3+ / V 4+ and Mn 2+ / Mn 3+ The undoped NMVP / C exhibited severe polarization, while molybdenum doping could significantly suppress this phenomenon. In addition, their initial discharge capacities were 95.7, 97.8, 100.1, 103.2, and 101.4 mAh g in order from low to high molybdenum doping content. -1 It can be seen that molybdenum doping helps to improve the reversible capacity and cycle stability of NMVP / C, and the modification effect is most prominent when the doping amount is 7.5 wt.%.
[0028] based on Figure 5 The rate performance diagram shows that different molybdenum doping contents improve the rate capacity of NMVP / C to varying degrees, among which the improvement effect is most significant when the molybdenum doping content is 7.5%. When the current density is restored to 1C, the NMMVP / C-0.075 electrode material still has a capacity of 90.0 mAh g -1 The reversible capacity is still higher than that of NMVP / C (77.3 mAh g -1 ), showing the superiority of molybdenum doping. Figure 6 The long cycle performance test results show that NMMVP / C-0.075 still has a capacity retention rate of 78.6% after 1500 cycles, which is much higher than NMVP / C material (62.1%). This fully reflects the effect of molybdenum doping on the cycle stability of sodium manganese vanadium phosphate materials. This is mainly due to the moderate sodium vacancy structure and reduced lattice volume generated by molybdenum doping, which improves the Na + The diffusion rate is increased while suppressing the volume expansion.
[0029] Figure 7 is Na in the present invention 3.85 Mn 0.85 Mo 0.075 The in-situ XRD patterns of the V(PO4)3 / C cathode material in the first two cycles clearly show that when charged to ~3.5 V, the diffraction peak moves to a lower angle, indicating a single-phase reaction. After continued charging, new diffraction peaks gradually appear, indicating a two-phase reaction. The Na atoms in the crystal structure of the sodium manganese vanadium phosphate-based material have two forms of coordination with oxygen atoms, one is hexacoordinated Na(1) and the other is octacoordinated Na(2), with an atomic ratio of 1:3. Due to the weak binding force between Na(2) and O, one Na(1) is released from NMVP / C in both the single-phase and two-phase reactions. + The Na(2) atoms are all Na(1) atoms, and the Na(2) atoms become unstable as the Na(1) atoms are released during the two-phase reaction, and gradually relax into the gap between Na(1) and Na(2), forming Na(3) atoms. In the molybdenum-doped sodium manganese vanadium phosphate-based material, the sodium vacancy structure caused by molybdenum doping and the additional loss of manganese elements cause it to release 0.85 Na(3) atoms during the two-phase reaction. + Therefore, NMMVP / C-0.075 has a Na + The process of extraction can be summarized as: first Na(1)Na(2) 2.85 MMVP / C-0.075 forms Na(1)Na(2) through a single-phase reaction 1.85MMVP / C-0.075, and then Na(2)Na(3)MMVP / C-0.075 is formed through a two-phase reaction. In addition, the phase evolution of the material during the discharge process reversibly repeats the charging process, and the phase evolution process of the second cycle also well repeats the first cycle process, further indicating that it has good electrochemical reversibility. At the same time, the volume change during the charge and discharge process is only ~3.8% calculated, indicating that molybdenum doping is beneficial to suppress the lattice change of NMVP / C during the cycle, which is beneficial to improve the cycle stability.
[0030] By comparing the electrochemical performance of NMMVP / C-0.075 and NMVP / C at 60 ℃ and -30 ℃ (2.5-3.8 V, 0.2C), the wide temperature range application possibility of molybdenum-doped sodium manganese vanadium phosphate-based materials was determined. Figure 8 As shown in the figure, the irreversible capacity of the two electrode materials is higher at high temperature, which is caused by the instability of the structure. At low temperature, there is a serious polarization phenomenon, which is related to the increase of its internal resistance and stress. In comparison, molybdenum doping greatly improves the disadvantages of NMVP / C at high and low temperatures. The initial discharge capacity of NMMVP / C-0.075 at -30 °C and 60 °C is 64.2 and 90.9 mAh g, respectively. -1 , which are higher than those of NMVP / C materials (48.4 and 81.3 mAh g -1 ).like Fig. 9 and Fig.10 As shown in the figure, NMVP / C and NMMVP / C-0.075 retained 68.9% and 81.3% of their reversible capacity after 100 cycles at 60 °C, respectively, and the capacity retention rates after 50 cycles at -30 °C were 88.1% and 93.6%, respectively. The high capacity retention rate at low temperature is related to the stable interface of the active material. The high reversible capacity and capacity retention rate of NMMVP / C-0.075 under harsh temperatures confirm its excellent wide temperature range adaptability, which means that molybdenum doping not only significantly improves the electrochemical performance of NMVP / C at room temperature, but also has outstanding modification ability at high and low temperatures.
Claims
1. A method for preparing a molybdenum-doped sodium manganese vanadium phosphate-based positive electrode material, characterized in that: The method uses transition metals to in-situ dope the manganese sites of sodium manganese vanadium phosphate, the general structural formula of which is Na4-2xMn1-2xMoxV(PO4)3 / C (x is the mass fraction of molybdenum doped in the manganese sites), and includes the following steps: (1) dissolving a sodium source, a manganese source, a molybdenum source, a vanadium source, a phosphoric acid source and a complexing agent in a suitable solvent, stirring and baking in a water bath or on an electric heating table until the mixture is in a gel state, and drying the mixture in a vacuum drying oven to obtain a precursor; (2) The precursor material in step (1) is ground evenly, pre-fired in an Ar atmosphere, pressed into tablets after being ground evenly, and then pre-fired and finally fired in an inert atmosphere. After being ground evenly, a high-valent molybdenum-doped sodium vanadium manganese phosphate positive electrode material can be obtained.
2. The method for preparing a molybdenum-doped sodium manganese vanadium phosphate-based positive electrode material according to claim 1, characterized in that: In step (1), the sodium source includes but is not limited to sodium acetate, sodium carbonate, sodium oxalate, sodium bicarbonate, and sodium citrate; the manganese source includes but is not limited to manganese acetate, manganese nitrate, and manganese oxalate; the molybdenum source includes but is not limited to molybdenum acetylacetonate and ammonium molybdate; the vanadium source includes but is not limited to ammonium metavanadate, vanadium pentoxide, vanadyl oxalate, and vanadium acetylacetonate; and the phosphate source includes but is not limited to diammonium hydrogen phosphate, ammonium dihydrogen phosphate, and phosphoric acid.
3. The method for preparing a molybdenum-doped sodium manganese vanadium phosphate-based positive electrode material according to claim 1, characterized in that: In step (1), the sodium source, manganese source, molybdenum source, vanadium source, and phosphoric acid source are weighed and mixed according to the element molar ratio of sodium: manganese: molybdenum: vanadium: phosphorus of 4:1:1-x:x:3 (0 < x ≤ 0.2).
4. The method for preparing a molybdenum-doped sodium manganese vanadium phosphate-based positive electrode material according to claim 1, characterized in that: The complexing agent in step (1) includes but is not limited to citric acid, glucose, ascorbic acid, oxalic acid, and oleic acid.
5. The method for preparing a molybdenum-doped sodium manganese vanadium phosphate-based positive electrode material according to claim 1, characterized in that: In step (1), the molar ratio of the complexing agent to the transition metal element in the sodium manganese vanadium phosphate-based positive electrode material is 1:
1.
6. The method for preparing a molybdenum-doped sodium manganese vanadium phosphate-based positive electrode material according to claim 1, characterized in that: Transition metals include high-valent molybdenum elements.
7. The method for preparing a molybdenum-doped sodium manganese vanadium phosphate-based positive electrode material according to claim 1, characterized in that: The solvent in step (1) includes but is not limited to water, ethanol, and tetraethylene glycol.
8. The method for preparing a molybdenum-doped sodium manganese vanadium phosphate-based positive electrode material according to claim 1, characterized in that: The heating temperature in step (1) is set to 60-95°C.
9. The method for preparing a molybdenum-doped sodium manganese vanadium phosphate-based positive electrode material according to claim 1, characterized in that: The drying method in step (1) is any one of vacuum drying, freeze drying and spray drying, the temperature is 80-200°C, and the time is 5-24h.
10. The method for preparing a molybdenum-doped sodium manganese vanadium phosphate-based positive electrode material according to claim 1, characterized in that: In step (2), the pre-sintering temperature is 300-500 °C, the time is 2-5 h, and the heating rate is 2-10 °C min -1 The pre-sintering pressure is 5-30 MPa, the final sintering temperature is 600-800 ℃, the time is 5-24 h, and the heating rate is 2-10 ℃ min -1 The inert gas includes but is not limited to argon, nitrogen, and hydrogen-argon mixture.
Citation Information
Patent Citations
Mo-doped polyanion positive electrode material, preparation method and application
CN115332529A
Polyanionic sodium ion battery positive electrode material and preparation and application thereof
CN116130621A
4d transition metal doped and modified vanadium manganese sodium phosphate positive electrode material and preparation method thereof
CN116826008A
Sodium vanadium phosphate material and preparation method thereof
CN117810408A